Description of Cyberbullying Behavior in Adolescents - Fitria, Yeni; Firnanda, Dhea; Kurniyawan, Enggal Hadi; Dewi, Erti Ikhtiarini; Laras Ati, Niken Asih (Babali Nursing Research, 2023)
Emotional enhancement as one of the characteristics of adolescence development causes adolescents vulnerable to juvenile delinquency such as bullying. In the current era of technological development, bullying is not only done directly but can also be done through social media or cyberbullying. This study aims to describe cyberbullying behavior in adolescents at Jember High School. This study aims to describe cyberbullying behavior in adolescents at Jember High School. The research method used was descriptive quantitative with 319 students in a high school in Jember Regency as a sample. The sampling technique uses proportionate stratified random sampling. The measurement tool used is The Second Revision of the Revised Cyber Bullying Inventory-II (RCBI-II) which has been translated and modified. The results showed that 13.8% of students became perpetrators, 17.9% became victims, 37.6% became both perpetrators and victims, and 30.7% were not involved. The conclusion from this study is that there is a high level of cyberbullying behavior in adolescents. There needs to be follow-up from the school to provide moral education, especially about the negative effects of cyberbullying on adolescent mental health as an effort to prevent cyberbullying behavior in students. In addition, parental supervision is also needed on adolescent activities in social media to minimize adolescent involvement in cyberbullying.